Stratégies d'autorégulation et synchronisation des temporalités dans un dispositif hybride : le rôle de l'évaluation - Najoua Mohib (Centre National d'Enseignement à Distance, 2018)
In this paper, we present a study on the effect of a blended learning module at Master level which learning outcomes were the development of project management competencies. Our objective was to better understand the impact of assessment on self-regulated learning as well as on time management in a module combining a Mooc and a face-to-face class. The analysis of students' interviews shows that, for the Mooc, frequency of assessment facilitates the elaboration of self-regulation strategies despite the constraints they impose, which then allows the synchronisation of the multiple temporalities of the training programme. Results highlight the role played by teachers in self-regulation processes and invite to further explore pedagogical potentialities of evaluation.